Food systems transformation commitments in Eastern Africa and their alignment with the UNFSS action areas and the Kampala CAADP Declaration - Jomo, Sofia; Mbao, Victor; Tiessen, Kevin H. D.; Robertson, Melanie (Frontiers in Sustainable Food Systems, 2025)
As we approach 2030, Africa remains distant from achieving the second sustainable development goal of zero hunger. Approximately 307 million people in Africa experience hunger, a number that may continue to rise. Therefore, it is imperative to urgently transform food systems to secure access to healthy and sustainable diets for all. Following the 2021 United Nations Food Systems Summit (UNFSS), countries developed commitments to transform their food systems. This paper aims to: (i) review the food system transformation commitments made by five Eastern African countries (Kenya, Uganda, Tanzania, Ethiopia, and Rwanda) following the UNFSS, and (ii) assess their alignment with the UNFSS action areas and the Kampala Comprehensive Africa Agriculture Development Program (CAADP) Declaration. The Food System Transformation Pathways (FSTPs) of each of the five countries were comprehensively reviewed and thematically analyzed. A total of 199 commitments were found. Regarding the UNFSS action areas, many commitments were focused on building resilience to vulnerabilities, shocks and stresses (n = 97), accelerating the means of implementation (n = 79), and advancing equitable livelihoods (n = 60). Regarding the Kampala Declaration, most commitments (n = 91) aligned with building resilient agrifood systems while only a few (n = 13) aligned with strengthening agrifood systems governance. Only 23.6% and 25.6% of the commitments aligned with nourish all people and food and nutrition security, respectively. While all the commitments indicate each country’s ambition in transforming their food systems towards healthiness and sustainability, none of the five country-level FSTPs outline a plan on how the commitments would be delivered, and only two commitments by Tanzania had explicit measurable metrics. Additionally, only Tanzania has so far developed a costed action plan for the implementation of the strategy. Since sustainable food systems are fundamental in promoting food and nutrition security, fostering social equity, and tackling climate change, it is essential for these countries to develop action plans with suitable indicators and monitoring and evaluation (M&E) frameworks to guide the implementation of their commitments. Countries should also regularly review their commitments to ensure their alignment with global and regional food systems transformation agendas, and that they are on track to achieve sustainability in their food systems.